PERK in POMC neurons connects celastrol with metabolism - Zhenyan He; Linh Lieu; Yanbin Dong; Sadia Afrin; Dominic Chau; Anita Kabahizi; Briana Wallace; Jianhong Cao; Eun-Sang Hwang; Ting Yao; Yiru Huang; Jennifer Okolo; et al. (JCI Insight, 2021)
ER stress and activation of the unfolded protein response in the periphery as well as the central nervous system have been linked to various metabolic abnormalities. Chemically lowering protein kinase R–like ER kinase (PERK) activity within the hypothalamus leads to decreased food intake and body weight. However, the cell populations required in this response remain undefined. In the current study, we investigated the effects of proopiomelanocortin-specific (POMC-specific) PERK deficiency on energy balance and glucose metabolism. Male mice deficient for PERK in POMC neurons exhibited improvements in energy balance on a high-fat diet, showing decreased food intake and body weight, independent of changes in glucose and insulin tolerances. The plant-based inhibitor of PERK, celastrol, increases leptin sensitivity, resulting in decreased food intake and body weight in a murine model of diet-induced obesity (DIO). Our data extend these observations by demonstrating that celastrol-induced improvements in leptin sensitivity and energy balance were attenuated in mice with PERK deficiency in POMC neurons. Altogether, these data suggest that POMC-specific PERK deficiency in male mice confers protection against DIO, possibly providing a new therapeutic target for the treatment of diabetes and metabolic syndrome.